The influence of capital structure and profitability on the solvency of nascent SMEs - Karikari Amoa-Gyarteng (University of Johannesburg, 2022)
Even though small and medium enterprises contribute significantly to the growth of national economies, they are vulnerable in their early stages and may fail. Hence younger businesses are more likely to fail than more established ones because they face complex challenges that may limit their viability. This is a notion established in the liability of newness framework. According to the liability of newness concept, the precarious existence of emerging organisations is due to difficulties in managing relationships among strangers, not quickly assembling resources, and not coping with difficult environments, among other issues. All these elements notwithstanding, previous literature suggests that small businesses can, and sometimes do engage in techniques or approaches to help reduce the liability of newness, such as raising adequate capital. This study suggests that not only is adequate capital important but that the right mix of capital also results in higher solvency, thereby mitigating the liability of newness. Because the various funding forms have distinct advantages and disadvantages, an appropriate capital structure reduces the cost of financing while increasing the value of the firm. This study also advances the idea that profitable businesses are productive and financially strong, and thus nascent enterprises with high profitability can minimise the liability of newness. As a result, the study sought to examine the influence of capital structure and profitability on the solvency of nascent small and medium enterprises. To put the study's hypotheses to the test, 1106 nascent small and medium enterprises that are registered with the National Board for Small Scale Industries were sampled across three major cities in Ghana. Thus, data was gathered from every member of the population. Such data, gathered from the SMEs' financial statements, was submitted to preliminary screening as well as a number of statistical measurements. Operationally, the dependent variable, solvency, was defined as the solvency ratio, working capital ratio, and net worth. As a result, three distinct regression models were developed for robustness. The study's findings broadly indicate that capital structure and profitability have an influence on the solvency of nascent small and medium enterprises. The study also determined that emerging small and medium enterprises should follow the principles of the pecking order theory to reduce the liability of newness. These findings, if adopted by SME owners, can aid in the maturation of their fledgling businesses.
Keywords: 330; Liability of Newness; Capital Structure; Nascent SMEs; Profitability; Solvency